Multiple trait sire evaluation using factor analysis in Sahiwal cattle - Gandhi, R S (The Indian Journal of Animal Sciences, 2007)
First lactation records (277) of Sahiwal cows were analyzed to evolve multi-trait criteria of selection like optimum selection index, standardized principal components scores (10) and indices based on principal components (2). The ranking of sires from the aforesaid criteria was compared with their ranking from first lactation 305-day or less. milk yield of their daughters. The genetic and phenotypic correlations among 5 first lactation traits namely AFC, FL305DMY, FLL, FDP and FSP were used to construct selection indices and to derive standardized principal components scores (PCSs). Out of different selection indices constructed by incorporating various traits in different combinations, an index having AFC, FL305DMY and FLL was considered to be optimum giving expected genetic gain of Rs 412.86 and accuracy of selection of 62.34%. Out of 10 principal components (PCs) constructed 5 each from genetic and phenotypic correlations, first 3 PCs from each set explained more than 85% of total variation of the population. Two more indices based on variance explained by first 3 principal components derived from genetic (I2) and phenotypic (I3) correlations were constructed. The rank correlation among sires from FL305DMY with optimum selection index (I1) and the indices derived from principal components (I2 and I3) were very high (&gt0.9). Similarly, the rank correlations of FL305DMY with majority of synthetic variables derived from principal components from both genetic as well as phenotypic correlations were near to unity. The rank correlations of optimum selection index with indices derived from principal components were 0.9575 (I2) and 0.9615 (I3) indicating that ranking of sires from optimum selection index was similar to the extent of 96% as compared to indices derived from principal components.